Clinical Relevance and Characteristics of Aspergillus calidoustus and Other Aspergillus Species of Section Usti - Emmanouil Glampedakis; Véronique Erard; Frederic Lamoth (Journal of Fungi, 2020)
The Aspergilli of section Usti (group ustus) are represented by over 20 species, of which Aspergillus calidoustus is the most relevant human pathogen. Invasive aspergillosis (IA) caused by these fungi is rare but could represent an emerging issue among the expanding population of patients with long-term immunosuppression receiving antifungal prophylaxis. Clinicians should be aware of this unusual type of IA, which often exhibits distinct clinical features, such as an insidious and prolonged course and a high occurrence of extra-pulmonary manifestations, such as skin/soft tissue or brain lesions. Moreover, these Aspergillus spp. pose a therapeutic challenge because of their decreased susceptibility to azole drugs. In this review, we outline the microbiological and clinical characteristics of IA due to Aspergillus spp. of section Usti and discuss the therapeutic options.